2021
DOI: 10.3389/fonc.2021.753330
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Matrix Characterization in Gastric Cancer Helps to Predict Prognosis and Chemotherapy Response

Abstract: The extracellular matrix (ECM) plays a central role in the formation of the tumor microenvironment. The deposition of the ECM is associated with poor prognosis in a variety of tumors. Aberrant ECM deposition could undermine the effect of chemotherapy and immunotherapy. However, there is no systematic analysis on the relationship between the ECM and prognosis or chemotherapy effect. In the present study, we applied the gene set variation analysis (GSVA) algorithm to score 2199 canonical pathways in 2125 cases o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 68 publications
1
16
0
Order By: Relevance
“…By comparing the stomach tissues of individuals with normal, premalignant, and malignant lesions, Zhao et al found that some collagen genes, such as COL4A1 and COL5A1, were significantly increased in malignant lesions of stomach compared with in premalignant lesions and were independent prognostic markers [24]. Further, ECM characterization in gastric cancer has been shown to predict treatment response and prognosis [25]. Thus, as more experimental and clinical observations are strongly indicating that ECM constituents, receptors and associated signaling molecules are promising biomarkers of prognosis and/or therapeutic targets; novel and more effective gastric cancer treatments that combine strategies targeting ECM with corresponding inhibitors or immuno-oncology agents could lead to improve therapeutic outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…By comparing the stomach tissues of individuals with normal, premalignant, and malignant lesions, Zhao et al found that some collagen genes, such as COL4A1 and COL5A1, were significantly increased in malignant lesions of stomach compared with in premalignant lesions and were independent prognostic markers [24]. Further, ECM characterization in gastric cancer has been shown to predict treatment response and prognosis [25]. Thus, as more experimental and clinical observations are strongly indicating that ECM constituents, receptors and associated signaling molecules are promising biomarkers of prognosis and/or therapeutic targets; novel and more effective gastric cancer treatments that combine strategies targeting ECM with corresponding inhibitors or immuno-oncology agents could lead to improve therapeutic outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Reportedly, signalling pathways that drive epithelial to mesenchymal transition (EMT) and the IGF1/IGF1 receptor pathway are substantially active in mesenchymal gastric cancer. 4 Additionally, a high extracellular matrix score is associated with a poor prognosis for gastric cancer, 5 and proteoglycans and glycosaminoglycans are regulators of cancer stem cell (CSC) function. 6 In general, the SIG500 genes were enriched in pathways associated with CSCs and the mesenchymal subtype of gastric cancer.…”
mentioning
confidence: 99%
“…For HER2-negative advanced GC patients, the primary treatment is still limited to platinum, fluoropyrimidine, and paclitaxel chemotherapeutic drugs ( 15 ). Furthermore, there are significant individual differences in prognosis even among patients at the same stage receiving the same treatment ( 10 , 18 , 49 51 ). Some patients clearly benefit from chemotherapy, while some patients do not and may have a worse prognosis due to the toxic effects of chemotherapy ( 10 , 16 , 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…The S-II was mainly enriched in ECM-related pathways. Interestingly, it has been reported in relevant studies that ECM can form a physical barrier to anticancer drugs ( 54 , 55 ) and prevent the effects of chemotherapy and immunotherapy, so the deposition of ECM is associated with poor prognosis of various tumors ( 49 ). One of the representative ECM genes, FBN1 , is up-regulated in S-II.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation